2012
DOI: 10.2319/060412-463.1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term therapeutic efficacy of oral appliances in treatment of obstructive sleep apnea-hypopnea syndrome

Abstract: OAs provided effective and safe long-term therapy for patients with OSAHS. Follow-up supervision is recommended since long-term alterations take place, although these appear to be minimal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 21 publications
0
24
0
1
Order By: Relevance
“…Some previous studies have reported that subjective feelings of bite changes decrease over time [6,9], while the degree of objectively assessed bite changes increases [1][2][3][4][5][6][7][8][9][10][11][12]16]. The patients included in the present study had used oral appliances for at least 3 years.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Some previous studies have reported that subjective feelings of bite changes decrease over time [6,9], while the degree of objectively assessed bite changes increases [1][2][3][4][5][6][7][8][9][10][11][12]16]. The patients included in the present study had used oral appliances for at least 3 years.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have used questionnaires where patients respond directly on paper [3][4][5][6][7][8][9][10][11][12] or in telephone interviews. It is not known whether the responses to the paper questionnaire were made totally beforehand, without any involvement on the part of the researchers, or were in some way influenced by the professional team.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Palatal length decreases and pharyngeal area increases in time. These changes can be due to the loss of edema caused by snoring and repetitive apneas [10,[32][33][34][35][36][37][38].…”
mentioning
confidence: 99%